Regular Banking System versus Shadow Banking System. A Comparative Assessment of Evidence from Romania - Baicu, Claudia Gabriela (Journal of Economic Development, Environment and People, 2019)
This study is determined by several factors that includes: (1) increasing interest in the shadow banking system as a result of the consequences of the global financial crisis; (2) the links between the traditional banking system and the shadow banking system with regard to the impact on financial stability; (3) low interest rates on bank deposits in recent years that might drive the development of the shadow banking system and (4) the lack of extensive literature on similar studies regarding Romania. The period analyzed is 2008-2018, beginning with the year when the effects of the global financial crisis were felt in Romania and the macroeconomic conditions deteriorated. The results reveal that the shadow banking in Romania is small compared to the regular banking system that dominates the Romanian financial system. The European Union financial sector greatly impacts both the banking sector and the shadow banking system. The entities and the activities composing the shadow banking system are not complex and the links between the two financial sectors raise greater risks to shadow banking entities than to regular banks.